1991
DOI: 10.1029/91jc02502
|View full text |Cite
|
Sign up to set email alerts
|

Retention of Greenland runoff by refreezing: Implications for projected future sea level change

Abstract: Melting produced at the surface of subfreezing permeable firn does not freely percolate but instead refreezes near its point of origin, raising the firn temperature and decreasing the pore space. If sufficient meltwater is introduced, the firn will warm to 0°C, and subsequent water will fill the remaining pore space without freezing. Only after the residual water content of the firn is exceeded will water flow through the firn and possibly escape as runoff. This process prevents summer melt on high Arctic glac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
239
3
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(246 citation statements)
references
References 14 publications
3
239
3
1
Order By: Relevance
“…While the basic processes associated with meltwater percolation through the snowpack and firn, with the potential for refreezing, have been extensively studied [25][26][27], major advances in recent years have resulted from extensive groundbased field campaigns in the percolation zone of the GrIS. The potential of porous firn to store refrozen meltwater, and thereby delay meltwater runoff, has been highlighted as a mechanism by which sea level rise could be considerably buffered for decades in a warming climate [28].…”
Section: Supraglacial Meltwater Processesmentioning
confidence: 99%
“…While the basic processes associated with meltwater percolation through the snowpack and firn, with the potential for refreezing, have been extensively studied [25][26][27], major advances in recent years have resulted from extensive groundbased field campaigns in the percolation zone of the GrIS. The potential of porous firn to store refrozen meltwater, and thereby delay meltwater runoff, has been highlighted as a mechanism by which sea level rise could be considerably buffered for decades in a warming climate [28].…”
Section: Supraglacial Meltwater Processesmentioning
confidence: 99%
“…Runoff is calculated using the Pfeffer et al (1991) meltwater retention and refreezing parameterisation with runoff occurring when surplus water is free to percolate downslope once firn is saturated. This model is limited in scope to a single season's accumulation layer, so may overestimate runoff in warm years as meltwater is unable to percolate into the earlier year's accumulation.…”
Section: Polar Mm5mentioning
confidence: 99%
“…A model-based study by Pfeffer et al (1991) showed that predictions of runoff-induced sea level rise from Greenland that did not consider meltwater refreezing within the firn could be overestimating sea level rise by as much as 5 cm over the next 150 years. The importance of meltwater retention was further highlighted by a study (Harper et al, 2012) based on field measurements obtained in 2007, 2008 and 2009 along the Expédition Glaciologique I nternationale au Groenland (EGIG) line in western Greenland.…”
Section: Introductionmentioning
confidence: 99%